1999
DOI: 10.1136/hrt.81.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of an impaired quality of life five years after coronary artery bypass surgery

Abstract: Objective-To identify determinants of an inferior quality of life (QoL) five years after coronary artery bypass grafting (CABG). Setting-University hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 31 publications
4
43
2
4
Order By: Relevance
“…Multiple studies have demonstrated that HRQOL improves, on average, after CABG [6,41,44,[46][47][48][49]. Specifically, physical function and mental health domains have been documented to improve post-CABG [41].…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have demonstrated that HRQOL improves, on average, after CABG [6,41,44,[46][47][48][49]. Specifically, physical function and mental health domains have been documented to improve post-CABG [41].…”
Section: Discussionmentioning
confidence: 98%
“…Other studies, however, show that diabetes is a predictor of QOL worsening after CABG. 11,20) Although the influence of diabetes to the appearance of neuropathy can be the cause of minor sensibility for each pain, even for angina although in this case is more important diabetes impact on the progression of coronary artery disease and the re-emergence of anginal pain. In addition, in diabetics with coronary disease, in comparison to non-diabetics, depression after serious cardiovascular events is more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Prädiktoren für eine erhöhte Mortalität nach Herzoperationen sind PAVK, zerebrovaskuläre Insuffizienz, Kreatinin-Erhöhung, Herzinsuffizienz, chronisch obstruktive Lungenerkrankung, Alter > 65 Jahre und die Notwendigkeit eines kombinierten Eingriffs. Vorbestehender Diabetes oder Notfalleingriffe sind nur Prädiktoren für eine erhöhte Morbidität [399][400][401][402][403].…”
Section: Patienten Nach Herzoperation Und Thorakotomie Evidenzunclassified